Limb Girdle Muscular Dystrophy Type 2E (Beta-Sarcoglycanopathy): A Case Report - Sarker, Shaoli; Ferdaus, Tafsira; Hoque, Asma; Uddin, Mohammed; Eshaque, Tamannyat Binte; Sarkar, Probir Kumar (Dhaka Shishu (Children) Hospital Journal, 2024)
Abstract not available DS (Child) H J 2023; 39(1): 56-60